2018
DOI: 10.1186/s12889-018-5070-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of two health education interventions to improve the varicella vaccination: a randomized controlled trial from a province in the east China

Abstract: BackgroundWe evaluated the effect of two Elaboration Likelihood Model (ELM)-based health educational interventions on varicella vaccine (VarV) vaccination among pregnant women in a province in the east China.MethodsA prospective randomized controlled trial was conducted among 200 pregnant women with ≥12 gestation weeks to test two interventions, including a messaging video and a messaging booklet. The participants were randomly assigned into the control group, the video group or the booklet group. The VarV cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 23 publications
1
8
0
4
Order By: Relevance
“…According our previous experience, communication channel made an important role in delivering the knowledge on immunization. 23 Hence, local public health officials might redesign the immunization information program to be more tailored to the specific subgroups of parents and might address the current safety concerns. Otherwise, the continued high vaccination coverage might be risky due to the refuse of vaccination among parents.…”
Section: Discussionmentioning
confidence: 99%
“…According our previous experience, communication channel made an important role in delivering the knowledge on immunization. 23 Hence, local public health officials might redesign the immunization information program to be more tailored to the specific subgroups of parents and might address the current safety concerns. Otherwise, the continued high vaccination coverage might be risky due to the refuse of vaccination among parents.…”
Section: Discussionmentioning
confidence: 99%
“…As more knowledgeable individuals are released into community, they may spearhead changes in their support systems. While education is inarguably important, studies have shown that educational interventions only modestly increase vaccine uptake in prison settings [31][32][33]. Therefore, novel educational approaches such as the adoption of a family-centred health promotion perspective [34], that is, expanding the provision of information to incarcerated individuals' support network, could be considered.…”
Section: Plos Onementioning
confidence: 99%
“…Estudo randomizado, realizado em 2018 no leste da China, aponta para maior cobertura vacinal nos dois grupos que receberam atividade de educação em saúde quando comparados ao grupo de caso controle. 20 Atividades de educação em saúde possibilitam a construção de atitudes preventivas de riscos e agravos e devem ser realizadas permanentemente, pois o processo de aprendizado contínuo proporciona novas concepções, atitudes e modificação na maneira de ser e de se cuidar. 21 Investigação realizada em Ouagadougou que analisou a completude vacinal da vacina hepatite B (recombinante) entre homens e mulheres, evidenciou resultado estatisticamente maior entre as mulheres quando comparadas aos homens, corroborando com os resultados encontrados nesta pesquisa.…”
Section: Materias E Métodosunclassified